An M/G/1 Retrial Queue with Fluctuating Modes of Services - Rajadurai, P.; Venkatesh, S.; Parameswari, K. (International Journal of Engineering and Technology, 2018)
In this paper, we consider a single server retrial queueing system with working vacation and two classes of customers, which are priority customers and ordinary customers. The single server provides fluctuating modes (optional phases) of services. Using the method of Probability Generating Function (PGF) approach and supplementary variable technique, the steady state results are obtained.Â